Workflow to spectral imagery calibration obtained in remotely piloted aircrafts (RPAs) by the empirical line method - Osco, Lucas Prado; Moriya, Érika Akemi Saito [UNESP]; Machado, Vagner Souza; Rezende Filho, Geison; Imai, Nilton Nobuhiro [UNESP]; Matsubara, Edson Takashi; Marcato Júnior, José; Ramos, Ana Paula Marques; Creste, José Eduardo (Universidade Federal do Rio de Janeiro, 2019)
The usage of Remotely Piloted Aircrafts (RPAs) in environmental studies increased over the past years due to the possibility of performing low-cost aerial image acquisition. However, these studies often need to extract physical information regarding the spectral conditions of a determined target. This paper aims to describe some of the fundamental steps on imagery acquisition and their calibration by using the empirical line method. A general workflow procedure was generated, and a case study applying the empirical line calibration application for RPA obtained imagery is discussed. We expect that the workflow serves as a guide for RPAs users throughout field planning and imagery processing in order to help they standardize and systematize their data acquisition and correction.
Fluxo de trabalho para a calibração de imagens espectrais obtidas em aeronaves remotamente pilotadas (ARPs) pelo método da linha empírica
Keywords: Calibration guide; Field spectroscopy; Radiometric correction